Remdesivir associated sinus bradycardia in patients with COVID-19: A prospective longitudinal study - Hajimoradi, Maryam; Sharif Kashani, Babak; Dastan, Farzaneh; Aghdasi, Sina; Abedini, Atefeh; Naghashzadeh, Farah; Mohamadifar, Arezoo; Keshmiri, Mohammad Sadegh; Noorali, Sima; Lookzadeh, Somayeh; Alizadeh, Niloufar; Siri, Mohammad Amin; et al. (Frontiers in Pharmacology, 2023)
Background: Remdesivir is effective against SARS-Cov-2 with little evidence of its adverse effect on the cardiac system. The aim of the present study is investigating the incidence of bradycardia in COVID-19 patients treated with Remdesivir. Method: This prospective longitudinal study was conducted in a tertiary center on COVID-19 patients for Remdesivir therapy. The objectives were to investigate the incidence of sinus bradycardia, and also the association between their demographics, underlying diseases, and the disease severity with developing bradycardia in COVID-19 patients treated with Remdesivir. Results: Of 177 patients, 44% were male. The mean (±SD) age of patients was 49.79±15.16 years old. Also, 33% were hospitalized due to more severe symptoms. Oxygen support was required for all hospitalized subjects. A total of 40% of the patients had comorbidities, with the most common comorbidity being hypertension. The overall incidence of bradycardia (heart rate<60 bpm) in patients receiving Remdesivir was 27%, of whom 70% had extreme bradycardia (heart rate <50 bpm). There was also a statistically significant reduction in heart rate after five doses of Remdesivir compared to the baseline heart rates. In the multivariable model, none of the covariates including age above 60 years, female sex, CRP>50 mg/L, O2 saturation<90%, underlying cardiovascular disease, hypertension and diabetes mellitus, and beta-blockers were associated with Remdesivir-induced bradycardia. No association was found between the COVID-19 severity indicators and bradycardia. Conclusion: As sinus bradycardia is a prevalent adverse cardiac effect of Remdesivir, it is recommended that all COVID-19 patients receiving Remdesivir, be evaluated for heart rate based on examination; and in the case of bradyarrhythmia, cardiac monitoring should be performed during administration to prevent adverse drug reactions.